Health risk assessment of heavy metals in shellfish collected from Fujian, China. Issue 3 (15th March 2020) - Li, Peng; Huang, Yu-Ying; Zeng, Jun; Lin, Zheng-Zhong; Huang, Zhi-Yong
Abstract: With industrialization and human activities, shellfish may be contaminated by various pollutants such as heavy metals. This study aims at the concentrations of As, Cr, Mn, Ni, Cu, Zn, Cd, Sn, Sb and Pb in shellfish collected from Fujian of China, and the risk of heavy metals in shellfish on human health based on target hazard quotients (THQ). Results showed that the THQ values of the elements were far below 1, except for As with an average value of 1.148 in razor clam. No detrimental health effects of heavy metals on humans health was observed by daily consumption of mussel and oyster, but the exposed population to short-necked clam, scallop and razor clam might experience noncarcinogenic health risks because each of the total THQ values was above 1 for the three shellfish.